Responsibility of Businesses With The Dropship System Reviewing From The Perspective of Law Number 8 of 1999 Concerning Consumer Protection - Ruslan Husein Marasabessy (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
Information technology has developed rapidly, and affects several aspects of human life, including buying and selling transactions. Online transactions allow sellers and buyers not to meet in person. The development emerged a new buying and selling system called dropship. Even in the trade law, buying and selling online is a concern. About selling IDX online has been explained in Law no. 7 of 2014 concerning Trade (Trade Law) and Law no. 8 of 1999 concerning Consumer Protection (Consumer Protection Law) is a reference for every business actor in conducting trade transactions, both conventional trading and trading through online or e-commerce. The purpose of this study is to describe how the views or interpretations of Law No. 8 of 1999 relate to the responsibilities of business actors who use the drop shipper system. The research method is a library reaseach. The results of this study are the positive law of dropshipping buying and selling law is permissible and the validity and terms of the agreement can be based on Law Number 11 of 2008 concerning Information and Electronic Transactions and Law Number 8 of 1999 concerning Consumer Protection where startups, especially Tokopedia, remain responsible answer in accordance with the provisions of law no. 8 of 2011.